Iš lokatyvų kilę latvių kalbos vietos prieveiksmiai - Judžentytė, Gintarė (Baltistica, 2008)
LATVIAN ADVERBS OF PLACE DERIVED FROM LOCATIVES This article analyzes Latvian adverbs of place derived from locatives. Locatives here are understood as the archaic pronominal locative (non-postpositive) and postpositive locatives, namely, the inessive, illative and allative. According to the said locatives, adverbs of places could be divided into 4 groups, i.e. 1) adverbs of place derived from the archaic pronominal locative; 2) adverbs of place derived from the inessive; 3) adverbs of place derived from the illative and 4) adverbs of place derived from the allative. Adverbialization is illustrated with examples from the old Latvian writings of G. Elger’s Evangelia et Epistolae and G. Mancelis’ Langgewünschte Lettische Postill.